The possible worlds. Hermeneutics of the Different hadith of Ibn Qutayba. (Journal of Human Sciences, 2023)
Possible worlds are among the terms that appeared in logical semantics, and the scholars’ interest in this term was related to their talk about the conditions for the veracity of sentences, and about describing sentences containing elements whose veracity cannot be verified in some worlds, or the nature of these worlds differs from the nature of known worlds.Looking at the Arab heritage, we note that some scholars dealt with the possible and the impossible from the semantic point of view, specifically Ibn Qutayba in the field of analyzing the Prophet's discourse, as his treatment of the problem of the concept of truth and lies was based on the concept of the multiplicity of worlds (possible worlds). His vision came in the context of responding to those who deny some phenomena that are not possible in the real world. Rather, the proponents of this vision deny, in the first place, the legitimacy of asserting the existence of a world separate from human experiences that language describes; Because the dominant paradigm from the social point of view of man's position and his environment turns into the concept of "the real world As opposed to other worlds that differ from this model and intersect with it. Ibn Qutayba noticed that some knowledge cannot be comprehended rationally if it is measured on the living world, and in order for us to understand and visualize it, we must visualize other worlds that are different from us and what we have spent in our lives. And he said: “And the people of denial did not bring this and its like, except by referring them to what is absent from them, to what is present with them, and making them do things according to what they know from themselves.”This research will answer a fundamental question, which is: How did Muslim scholars deal with the contradictions of discourse (language) with the world?, which will raise some other questions that we intend to answer in the folds of the research.Ibn Qutbah took the concept of the multiplicity of worlds, a procedural approach, in the semantic analysis of the Prophet's hadith, and access to the significance of his speech. Therefore, in this paper, we will seek to demonstrate Ibn Qutayba's approach to the concept of the multiplicity of worlds (possible worlds) within the interpretation of the problem from the hadith of the Prophet, by means of a descriptive and analytical approach to explain and analyze the phenomenon.